Pemberdayaan Masyarakat Pesisir Desa Kutawaru Cilacap Melalui Inovasi Pangan Lokal Berbasis Buah Mangrove Rhizophora Mucronata - Mardiyana; Ulikaryani; Nurakhlis Sarihidaya Laksana (Politeknik Negeri Cilacap, 2026)
Kutawaru Village is a coastal village in Cilacap Regency with significant potential for local food innovation based on mangrove resources. The Kutawaru Independent Community Group (MAMAKU) had not previously utilized mangrove fruits, particularly Rhizophora mucronata, as food products. This community empowerment program was conducted through socialization and hands-on training on processing mangrove fruits into flour and derivative products such as cookies. The program applied an Asset Based Community Development (ABCD) approach, focusing on local natural assets in the form of Rhizophora mucronata mangrove vegetation surrounding the partner area. The results showed an increase in community empowerment, reflected in improved knowledge and practical skills in mangrove fruit processing. Participants’ understanding increased from 38.5% with no understanding, 53.8% with limited understanding, and 7.7% with sufficient understanding to 100% of participants being able to understand and independently practice mangrove fruit processing.